Ironic Freedom : Personal Choice, Public Policy, and the Paradox of Reform - Baer, Judith A.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2013)
Ironic Freedom asserts that freedom from governmental interference may make people vulnerable to other sources of coercion; these affects vary by gender, race, and class. Increasing negative freedoms may reinforce existing asymmetrical power relationships within society.
Keywords: Social sciences; Political theory; World politics; Europe -- Politics and government; Political philosophy; Social sciences -- Philosophy; Political sociology; Social Sciences; Political Theory; Political Philosophy; European Politics; Social Theory; Political History